The cystathionine‐β‐synthase domains on the guanosine 5′'‐monophosphate reductase and inosine 5′‐monophosphate dehydrogenase enzymes from Leishmania regulate enzymatic activity in response to guanylate and adenylate nucleotide levels. Issue 5 (10th March 2016) - Smith, Sabrina; Boitz, Jan; Chidambaram, Ehzilan Subramanian; Chatterjee, Abhishek; Ait‐Tihyaty, Maria; Ullman, Buddy; Jardim, Armando
Summary: The Leishmania guanosine 5′‐monophosphate reductase (GMPR) and inosine 5′‐monophosphate dehydrogenase (IMPDH) are purine metabolic enzymes that function maintaining the cellular adenylate and guanylate nucleotide. Interestingly, both enzymes contain a cystathionine‐β‐synthase domain (CBS). To investigate this metabolic regulation, the Leishmania GMPR was cloned and shown to be sufficient to complement the guaC ( GMPR ), but not the guaB ( IMPDH ), mutation in Escherichia coli . Kinetic studies confirmed that the Leishmania GMPR catalyzed a strict NADPH‐dependent reductive deamination of GMP to produce IMP. Addition of GTP or high levels of GMP induced a marked increase in activity without altering the Km values for the substrates. In contrast, the binding of ATP decreased the GMPR activity and increased the GMP Km value 10‐fold. These kinetic changes were correlated with changes in the GMPR quaternary structure, induced by the binding of GMP, GTP, or ATP to the GMPR CBS domain. The capacity of these CBS domains to mediate the catalytic activity of the IMPDH and GMPR provides a regulatory mechanism for balancing the intracellular adenylate and guanylate pools. Abstract : Thecystathionine‐ β ‐synthase domains on the guanosine 5′‐monophosphate reductase and inosine 5′‐monophosphate dehydrogenase enzymes from Leishmania regulate enzymatic activity in response to guanylate and adenylate nucleotide levels